2016
DOI: 10.1007/s00005-016-0393-y
|View full text |Cite
|
Sign up to set email alerts
|

Does TSH Trigger the Anti-thyroid Autoimmune Processes? Observation on a Large Cohort of Naive Patients with Thyroid Hemiagenesis

Abstract: Thyroid hemiagenesis (THA) is a rare abnormality characterized by the absence of one thyroid lobe. Elevated thyroid stimulating hormone (TSH) level and higher incidence of thyroid diseases were reported in THA. The aim of the study is to evaluate the thyroid autoimmunity incidence in patients with THA and influence of higher than average TSH level on thyroid volume (TV) and its change with age. The study included a group of naive patients with THA and a control group of subjects with bilobate thyroid. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In addition, it is unlikely that the TSHR A-subunit transgene contributed to thyroid hemiagenesis in 1 mouse because (a) it occurred in 2 wild-type NOD.H2 h4 mice and (b) the transgene is located on chromosome 1 [17] and not on chromosomes 2, 12, 5, and 16, the locations of Pax 8, TTF1, Shh, and Tbx1. It should be emphasized that the genetic basis for thyroid hemiagenesis in humans could be identified in only a minority of cases with no common or specific gene identified [3,38], although thyroid autoimmunity was frequently present [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is unlikely that the TSHR A-subunit transgene contributed to thyroid hemiagenesis in 1 mouse because (a) it occurred in 2 wild-type NOD.H2 h4 mice and (b) the transgene is located on chromosome 1 [17] and not on chromosomes 2, 12, 5, and 16, the locations of Pax 8, TTF1, Shh, and Tbx1. It should be emphasized that the genetic basis for thyroid hemiagenesis in humans could be identified in only a minority of cases with no common or specific gene identified [3,38], although thyroid autoimmunity was frequently present [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Szczepanek-Parulska et al. [ 43 ] reported in their study group a higher prevalence of thyroid antibodies in patients with THA compared with individuals with normal thyroid glands, thus suggesting evidence that THA may also promote the development of immune thyroid disorders.…”
Section: Clinical Consequences Of Thyroid Hemiagenesismentioning
confidence: 93%
“…Because patients with THA seem to be prone to hypothyroidism, regular control of thyroid hormones, in particular TSH, seems to be warranted to detect any thyroid dysfunction at an early stage. Due to the higher reported rate of autoimmune disorders in THA [43], a consequent evaluation of thyroid antibodies seems to be warranted when THA has been diagnosed.…”
Section: Clinical Consequences Of Thyroid Hemiagenesismentioning
confidence: 99%
“…Szczepanek-Parulska et al in 2016, performed a large cohort study of sixty-five patients with THA and revealed a high prevalence of elevated thyroid auto-antibodies with patients having more clinical manifestation of thyroid autoimmune pathology [ 38 ]. This could be attributed to a hypothesis in which excessive stimulation of TSH receptors may lead to the “leak” of some thyroid autoantigens such as thyroglobulin or thyroid peroxidase into the circulation leading to an autoimmune response and resultant autoantibody thyroid development [ 39 ].…”
Section: Reviewmentioning
confidence: 99%